Efficient and privacy-preserving decentralized energy trading scheme in a blockchain environment. (November 2022) - Dong, Jingya; Song, Chunhe; Zhang, Tao; Hu, Youjun; Zheng, Hao; Li, Yuanjian
Abstract: Blockchain technology provides the possibility for the realization of decentralized energy trading. However, the blockchain confronts privacy risks and efficiency issues, which hinder its application in energy trading. In this paper, to solve this problem, we propose an efficient and privacy-preserving decentralized energy trading scheme in a blockchain environment. We propose an account mapping algorithm to solve the privacy attack problem. We propose a new transaction processing method, which can protect private data and improve execution efficiency by two-layer transaction processing. Finally, we verify the effectiveness of the proposed scheme for privacy protection and trading efficiency of decentralized energy transactions through experiments.